BIO-SURVEILLANCE DES METAUX LOURDS (PB, ZN, CU) A LA SORTIE DE LA STATION D’EPURATION DE TIARET (ALGERIE) AU MOYEN DES VEGETAUX AQUATIQUES: PLANTE LEMNA MINOR, ALGUE SPYROGYRA LINK SP ET BROYOPHYTE FONTINALIS ANTIPYRETICA - Meriem, Chafaa; M’hamed, Maatoug; Tandlich, Roman; Benchaben, Hellal; Mohamed, Ait Hammou (European Scientific Journal, ESJ, 2015)
An original device has been developped and valided to monitor water quality with aquatic plants at the exit of wastewater treatment with plants in ain bouchakifin tiaret (algeria). This device or « bio-station » has provided first particularly interesting results: the selected bio-indicator plants (lemna minor ,spyrogyra link sp and fontinalis antipyretica) are able on one hand to grow in the effluents with a significant accumulation of heavy metals, and on the other hand to detect these micro-pollutants even when they are undectable in effluents. The results obtained during this study, have revealed severe contamination of purified wastewater with heavy metals specially lead, zinc and copper, the values recorded for pb are 29,17 ± 25,66 ug/g (spyrogyra link sp), 48,43 ± 39,07 ug/g (fontinalis antipyretica) et 16,78 ± 12,37 ug/g (lemna minor). The highest values were observed for copper and zinc accumulated by these plants for copper are: 275,93 ± 235,20 μg/g, 416,52 ± 285,88 ug/g and 213,92 ± 137,07 ug/g respectively. By against, the concentrations recorded for zinc are 917,04 ± 654,40 ug/g , 1040,48 ± 848,34 ug/g and 545 ± 368,76 g/g respectively. It therefore appears that a "bio-station" equipped sentinel plants sentinel can be an efficient and economical complementary device for continuously monitoring contamination waste water from treatment plants prior to their arrival at the dams.